Youth Restiveness and Socio-Economic Development and Their Implications on National Security: A Sociological Perspective. (Abuja Journal of Sociological Studies, 2026)
The incessant restive activities of Nigerian youths and their implications on national security have made it a contemporary issue in Nigerian society. Youth restiveness, characterised by widespread agitation, violence, and social unrest, has become a pervasive issue in many Nigerian societies, threatening national security and socioeconomic development. Despite various interventions, the problem persists, undermining efforts to achieve national security and socio-economic development. This study aims to investigate the sociological elements that contribute to youth restiveness in Nigeria, as well as the consequences for national security, in order to propose effective solutions for reducing these difficulties while also supporting national security and socioeconomic growth. This research investigates the relationship between youth restiveness and socioeconomic development, as well as its implications for national security.  It used the deprivation-frustration-aggression theoretical framework. The multistage sampling procedure was used to select 399 respondents from the study population.  The data in the paper comes from both primary and secondary sources. The recommendations include, among other things, that the government at all levels, especially local government, should develop a culture of entrepreneurship by supporting, training, and rewarding self-reliant youths across the nation, and that creating jobs and employment opportunities for the youth would prevent them from engaging in any restive activities because unemployment makes them willing tools in any conflict. This strategy would encourage youth productivity by providing entrepreneurial innovation, creativity, and invention.